2018
DOI: 10.1139/cjas-2016-0136
|View full text |Cite
|
Sign up to set email alerts
|

Production of Jiggs bermudagrass and the impact of quality milk production and quality of Holstein dairy cows under an intermittent grazing system

Abstract: Dairy production plays a fundamental role in the Brazilian economy, and high-17 quality forage is necessary for ruminants to produce satisfactory milk levels, so the aim of the 18 present study was to evaluate the production and quality of Jiggs bermudagrass and its effects 19 on the production and quality parameters of milk from Holstein cows under an intermittent 20 grazing system throughout the year. The experiment was conducted in a randomized design 21 with the four seasons as treatments was replicated fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Even with the use of irrigation in these seasons, forage production was lower than in the other seasons, producing 49% in relation to summer and 33.2% in relation to spring and fall. Also, in these periods, in the same experimental area, Brandstetter et al (2018) observed a greater elongation of stems, where the le af: stem ratio declines rapidly, because in addition to the higher stem growth, leaf appearance (fundamental for dry mass production) was reduced due to the lower quantity and quality of the light that reaches the inside of the canopy. As a result, there was an increase in fractions C, which also reflected lower milk yield (Brandstetter et al, 2018).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Even with the use of irrigation in these seasons, forage production was lower than in the other seasons, producing 49% in relation to summer and 33.2% in relation to spring and fall. Also, in these periods, in the same experimental area, Brandstetter et al (2018) observed a greater elongation of stems, where the le af: stem ratio declines rapidly, because in addition to the higher stem growth, leaf appearance (fundamental for dry mass production) was reduced due to the lower quantity and quality of the light that reaches the inside of the canopy. As a result, there was an increase in fractions C, which also reflected lower milk yield (Brandstetter et al, 2018).…”
Section: Resultsmentioning
confidence: 75%
“…Also, in these periods, in the same experimental area, Brandstetter et al (2018) observed a greater elongation of stems, where the le af: stem ratio declines rapidly, because in addition to the higher stem growth, leaf appearance (fundamental for dry mass production) was reduced due to the lower quantity and quality of the light that reaches the inside of the canopy. As a result, there was an increase in fractions C, which also reflected lower milk yield (Brandstetter et al, 2018). The results found for fraction C herein (Table 1) are lower than those observed by Branco et al (2012), who evaluated the chemical composition and fractionation of crude protein of the Coastcross grass, and reported values of 14.73, 14.98 and 15.01% for winter, spring and summer, respectively.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations